A comparison of integrated pest management and traditional practices for bagged maize stored in Nigeria. (March 2020) - Ala, Adeola A.; Otitodun, Grace O.; Ajao, Shekinat K.; Nwaubani, Samuel I.; Opit, George P.; Ogundare, Moses O.; Braimah, Jafar A.; Busari, Gbenga S.; Abel, Grace I.; Omobowale, Mobolaji O.; Olenloa, Akhere E.; Ogwumike, Jonathan C.; et al.
Abstract: In grain markets in Nigeria, stored product insects can cause significant losses in quality and quantity of stored grains. Insect infestations in storehouses are usually controlled by the unilateral use of chemical insecticides, which have unintended adverse effects. In this study, approximately 15 MT of well-dried, Aflasafe™-treated maize was procured from a local farm settlement in January 2016. It was subsequently fumigated, mechanically cleaned and placed in 100-kg polypropylene bags for storage. The study was conducted during February–December 2016, to compare the effectiveness of traditional storage practice (TSP) with integrated pest management (IPM) practice. IPM for warehouse facilities focuses on adequate drying, inspection and cleaning of storehouses and their surroundings and regular examination of grain (IPMD). Traditional storage practice generally has little or no sanitation of the facility or regular examination of grain (monitoring) for insect pests. Study locations were markets in Ibadan, Oyo and Ilorin towns in Southwest and Northcentral Nigeria, respectively. Each market had two storehouses where TSP or IPMD was assigned; each storehouse had twenty-five bags of maize, which were sampled monthly to assess the effects of the two practices on stored maize insect populations and quality. Generally, from October to December, there tended to be more insects of all species in TSP than IPMD. Percent insect damaged kernels (%IDKNB) and weight loss (%WL) were also higher in TSP than IPMD during the October–December period. Percent germination in December was higher in IPMD (96.3%) than in TSP (85.3%). Aflatoxin levels in both TSP and IPMD did not exceed 1.9 ppb. Data from this study show that IPMD results in lower stored-product insect population levels and better maize quality than TSP. Thus, IPMD practice needs to be more widely adopted in storehouses in Nigeria and the rest of sub-Saharan Africa. Highlights: IPMD results in lower stored-product insect pest population levels than TSP. IPMD results in better maize quality than TSP. Regular examination of bagged grain needs to be conducted throughout storage. Proper drying and disinfestation before storage facilitate grain preservation. Aflasafe keeps aflatoxin levels of well dried stored maize at safe levels.